CT scan assessment of Olfactory Fossa in Kirkuk adult population prior to sinus surgery - Hussein, Karim Mahmood (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: The fovea ethmoidalis and the lateral lamella of the cribriform plate of the ethmoid bone are the parts of the skull base that are most vulnerable to iatrogenic problems during functional endoscopic sinus surgery. The vertical height of the cribriform plate's lateral lamella, which is divided into three groups based on Keros types. According to the Keros, The likelihood of iatrogenic injury and issues increases with the cribriform plate's lateral lamella height. Aim of the study: The aim of this study is to assess the discrepancies in the ethmoid roof elevation (the depth of the olfactory fossa) amongst the adult Kirkuk population using multi-detector computed tomography. Patients and methods: 160 persons who were referred for a CT scan to evaluate their paranasal sinuses participated in the study. Participants in this study were not allowed to have any pathological abnormalities affecting the ethmoid roof. According to the Keros classification, which was split into three groups (Keros I from 1 to 3 mm, and from 4 to 7 mm considered Keros II, while Keros III should be from 8 mm and more), the vertical height of the lateral lamella of the cribriform plate was measured using the coronal portion of a CT image. Results: The patients' average age was 35.25 ±14.16 years. The range of the left lateral lamella height is 2.1 to 10.0 mm, and the range of the right lateral lamella height is 2.0 to 9.9 mm. Of these, 43.75% had Keros type I, 55% had Keros type II, and 1.25% had Keros type III. Conclusion: Keros type II was present in the majority (about 55%) of the adult population in that was studied while Keros type I was (about 43.75%). However, just (about 1.25%) of the adults population in the sample had Keros type III.